Seasonal changes in physiological responses and body composition during a competitive season in male and female elite collegiate ice hockey players - Delisle-Houde, P.; Reid, R. E. R.; Insogna, J. A.; Chiarlitti, N. A.; Andersen, R. E. (The Journal of Strength and Conditioning Research, 2019)
Ice hockey continually overloads athletes with limited time for recovery, which may affect several physiological responses and alter body composition. The purpose of this study was to identify changes in physiological parameters and body composition profiles over the competitive season in elite collegiate ice hockey players. Forty-four players, 24 males (age = 22.7 ± 1.3 years, height = 1.82 ± 0.6 m, and body mass = 86.87 ± 6.44 kg) and 20 females (age = 19.9 ± 1.8 years, height = 1.66 ± 0.7 m, and body mass = 68.76 ± 5.91 kg) participated in 4-minute submaximal exercise tests and body composition assessments at pre-season, mid-season, and end-season. Changes in physiological parameters and body composition were analyzed using repeated-measures analysis of covariance controlling for age. Males' postexercise blood lactate concentration decreased (p = 0.05) from pre- to mid-season (9.3 vs. 6.2 mmol/L) and increased (p = 0.05) from mid- to end-season (6.2 vs. 8.0 mmol/L). Heart rate increased (p = 0.05) after the third and fourth minute of the submaximal test in both sexes from pre- to end-season and from mid- to end-season. Males' body fat percentage decreased (p = 0.05) from mid-season (17.4 vs. 16.1%), whereas increases were observed (p = 0.05) in both sexes from mid- to end-season. This study produced evidence that male and female collegiate hockey athletes' physiological responses and body composition profiles change over the season. Sport scientists working with collegiate hockey teams, may need to revise annual training programs to attenuate reductions in fitness and hopefully prevent injuries.